Book review: Salt tectonics. Principles and practice, by Martin P.A. Jackson and Michael R. Hudec, 2017. Cambridge University Press, Cambridge. 498 pages. Hardback: price £64.99. ISBN 978-1-107-01331-5. - Krzywiec, Piotr (Geologos, 2019)
Book review: Salt tectonics. Principles and practice, by Martin P.A. Jackson and Michael R. Hudec, 2017. Cambridge University Press, Cambridge. 498 pages. Hardback: price £64.99. ISBN 978-1-107-01331-5